A NEW GENUS, TWO NEW SPECIES AND TWO NEW RECORDS OF WHITEFLIES (ALEYRODIDAE: HEMIPTERA) FROM INDIA - PHILLIPS, ANNIE; JESUDASAN, R. W. ALEXANDER (The Bioscan, 2013)
A study on the systematics of whiteflies from the campus of Madras Christian College, Tambaram, Tamil Nadu, India was conducted between August 1999 and December 2002. From the study two new species of whiteflies have been determined - one species named Dialeurodes megaspina and the other assigned to a new genus Milleraleurodes with a new species illuminata. Dialeurodes radiipuncta (Quaintance and Baker) and Dialeuropora murrayae (Takahashi) are reported for the first time from India.